Labor Market Inequalities in FYR Macedonia : New Evidence on Gender and Ethnicity - World Bank (Washington, DC, 2015)
The study includes an analysis of inequality patterns in terms of labor force participation as well as a review of policy responses, and areas for possible further policy action. In particular, the report looks at the two main dimensions of inequality that characterize Macedonia’s labor market: gender and ethnicity. Almost half the female working age population is inactive, whereas male inactivity is considerably lower. Labor market outcomes also vary significantly with ethnicity. In particular, a strong interaction exists between gender and ethnicity, with ethnic minority women forming a particularly vulnerable group. Hence, it is worthwhile to investigate in more detail how gender and ethnicity shape the Macedonian labor market, and how public policy could be used to increase labor market participation and job opportunities for women and ethnic minorities. This report is organized as follows. First, the report describes the main characteristics of the Macedonian labor market, emphasizing the most important patterns of inequality in terms of labor market participation (section two). Section three addresses the possible causes of these inequality patterns. Section four discusses potential policy responses and concludes.